CARDIOVASCULAR RISK BEFORE AND AFTER SURGICAL TREATMENT OF SEVERE OBESITY - Lilian CARDIA; Alexandre Viera GADDUCCI; Denis PAJECKI; Marco Aurelio SANTO; Roberto DE CLEVA (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT BACKGROUND: Obesity is a predisposing factor for serious comorbidities, particularly those related to elevated cardiovascular mortality. The atherogenic index of plasma (AIP) has been shown to be a useful indicator of patients with insulin resistance. AIMS: The aim of this study was to assess cardiovascular risk before and after surgical treatment of obesity. METHODS: A total of 615 patients undergoing bariatric surgery between 2007 and 2012 were evaluated using the analysis of electronic records (triglyceride/high-density lipoprotein cholesterol) before and after surgery. The AIP levels >3.5 mg/dL for men and >2.5 mg/dL for women were insulin-resistant and predisposed to cardiovascular events. RESULTS: A total of 117 men had an AIP >3.5 mg/dL during the preoperative period, 13.5% during the early postoperative period, 14.3% during the intermediate period, and 18.2% during the late postoperative period. Among 498 women, 56.2% had an AIP >2.5 mg/dL before surgery, 17.9% in early postoperative period, 13.5% in the intermediate period, and 11.4% in the late period. CONCLUSIONS: Bariatric surgery resulted in a significant effect on the AIP, insulin resistance, metabolic syndrome, and therefore, the risk of cardiovascular diseases.